Student-Teachers’ Engagement in Mediated Writing Feedback: Narrative Inquiry - Muhammad Reza Pahlevi (Journal of English Language Teaching and Linguistics, 2020)
Advance of technology brings about different ways in language learning and teaching. Indeed, mediated writing feedback has been adopted and demanded in language assessment. However, little is known on how students’ engagement in mediated writing feedback. This present study explores students’ engagement in mediated writing feedback. Narrative inquiry design was used to reveal students’ experience and reflection of mediated writing feedback. Three student-teachers involved in this study. They assigned as they meet requirement in this study. They were in thesis writing. Semi-structured interview used to reveal students’ learning experience in receiving mediated writing feedback. Students’ writing work used in this study as well. The obtained data were analyzed by thematic analysis. They also interpreted by theories lenses. The findings illustrated that mediated writing feedback stimulates students learn to write actively (behavior engagement), assists students learn to write (cognitive engagement), and have a balance emotion (emotional engagement.)